1998
DOI: 10.1007/pl00009011
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium, Zinc, Copper, Silver and Chromium(III) removal from wastewaters by Sphaerotilus natans

Abstract: Living cells of Sphaerotilus natans are used for heavy metal's (Cd, Zn, Cu, Ag, and Cr) removal from aqueous solutions simulating the polluting power of acid industrial wastewaters. At low metal concentrations (<25 mg/l) this microorganism is able to remove within 8± 15 days Cd, Zn, Cu, and Ag with excellent yields (from 81 to 99%) often increasing with starting metal concentration. The yield observed for Cr(III) removal, never exceeding 60%, is not appreciably in¯uenced by the starting biomass level; in addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
14
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 14 publications
7
14
0
Order By: Relevance
“…This suggests that sorption of the metal ions involve two species, in this case, the metal ion and the biomass (Herrero et al, 2008). These results are in accordance with similar researches carried out (Ho et al, 2004;Kumar et al, 2006;Lodi et al, 1998) with several natural sorbents. The time profile for the various metal ions studied on L. cylindrica is presented in Figure 5.…”
Section: Resultssupporting
confidence: 89%
“…This suggests that sorption of the metal ions involve two species, in this case, the metal ion and the biomass (Herrero et al, 2008). These results are in accordance with similar researches carried out (Ho et al, 2004;Kumar et al, 2006;Lodi et al, 1998) with several natural sorbents. The time profile for the various metal ions studied on L. cylindrica is presented in Figure 5.…”
Section: Resultssupporting
confidence: 89%
“…Either the single mechanism or a combination of these well regulatory mechanisms helps the bacterial cell to retain essential quantity of zinc and to avoid the toxic concentration of zinc to build up inside the cell. Lodi et al (1998) reproduced the results of biosorption of zinc from liquid phase. The authors reported that under the theory of mass transfer, metal ion biosorption on microbial cell surface was mediated by simple biosorption as well as by the movement of metallic ions inside the cells.…”
Section: Biological Removal Of Zinc By Microorganismssupporting
confidence: 55%
“…1), the final cell mass concentration decreased by approximately 35% and 70% using 7.5 mg/L (run 2) and 15 mg/L (run 3) of Cd, respectively. The ability to remove Cd by different living microorganisms, among which Sphaerotilus natans [25,26], Zoogloea ramigera [27], and Rhizopus arrhizus [28], was already demonstrated. In almost all cases, the toxic effect of such a metal was related to a biosorption mechanism mediated by specific carriers [25,29]; therefore, taking into account its abiotic nature along with its low incidence in the environment, one can think to a mechanism of cell penetration in competition with some other biotic metal.…”
Section: Resultsmentioning
confidence: 99%